Law Enforcement of Corruption Offenses in Village Budget (APBDes) Development Sector of Salaon Dolok Village Government (Analysis of Court Decision Number: 49/Pid.Sus-TPK/2023/PN Mdn) - Sintia Andayani; Kusbianto Kusbianto; Ida Nadirah (Yayasan Kawanad, 2025)
This study reviews the judicial decision of the Medan District Court Number 49/Pid.Sus-TPK/2023/PN Mdn on corruption in village fund management (APBDes) in the development sector. In this case, village officials committed authority abuse by falsifying accountability documents, diverting budgeted funds to cover up previous audit findings, and leaving planned physical infrastructure projects uncompleted. The trial's evidentiary process relied on documentary evidence including accountability reports, disbursement records, and details of suspicious transactions plus forensic audit results that confirmed state financial losses amounting to Rp383,896,956.97 as well as witness testimonies supporting these irregularities. Effective law enforcement requires a complete investigation and prosecution with coordination and sanctions proportionate to the crime so that it can serve as a deterrent for similar future acts; however, the quality of judicial decisions and public confidence are still affected by internal problems such as inconsistent integrity and professional capacity of law enforcement personnel, together with external problems such as political interference, inadequate supervision mechanisms, low community legal awareness, and insufficient witness protection. Strengthening institutional independence, inter-agency coordination, oversight intensity, and sustained legal education for communities are essential to achieving greater consistency and credibility in handling village budget corruption cases.